2017
DOI: 10.1038/s41598-017-03847-x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative modelling of hip fracture trends in 14 European countries: testing variations of a shared reversal over time

Abstract: Qualitative similarities between hip fracture trends in different countries suggests variations of the same epidemic. We tested a single statistical shape to describe time trends in Europe, while allowing for country-level variability. Using data from 14 countries, we modelled incidence rates over time using linear mixed-effects models, including the fixed effects of calendar year and age. Random effects were tested to quantify country-level variability in background rates, timing of trend reversal and tempo o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 44 publications
3
14
0
2
Order By: Relevance
“…Taken together, this study confirms that Danish hip fracture rates continued to decline from 2005 to 2015 parallel to the decrease in most other European countries [21] against a backdrop of stagnating use of drugs licensed for osteoporosis. Prior epidemiological studies have suggested that this is mainly caused by a protective cohort effect specific to women born in the 1930s [22] which will be followed by a return to higher age specific fracture rates, with the hip fracture burden further magnified by the increase in the number of the oldest old in Northern Europe and in the number of persons at high risk of fracture [23].…”
Section: Accepted Manuscript 11supporting
confidence: 76%
“…Taken together, this study confirms that Danish hip fracture rates continued to decline from 2005 to 2015 parallel to the decrease in most other European countries [21] against a backdrop of stagnating use of drugs licensed for osteoporosis. Prior epidemiological studies have suggested that this is mainly caused by a protective cohort effect specific to women born in the 1930s [22] which will be followed by a return to higher age specific fracture rates, with the hip fracture burden further magnified by the increase in the number of the oldest old in Northern Europe and in the number of persons at high risk of fracture [23].…”
Section: Accepted Manuscript 11supporting
confidence: 76%
“…Sweden has one of the highest incidence rates of fall-related injuries and fatal falls among older adults in Europe 1. Falls often cause serious physical injuries (eg fractures), that in turn lead to functional impairment, disability, reduced social activities, lowered quality of life, and increased risk of mortality 2,3.…”
Section: Introductionmentioning
confidence: 99%
“…A study on 14 European countries indicated the predicted maximum hip fracture incidence rate from 376 per 100,000 population in Portugal to 1390 per 100,000 population in Sweden among females, and from 157 per 100,000 population/year in Portugal to 742 per 100,000 population/year in Sweden among males . (26) The results of this study, however, should be interpreted with caution because of differences in number of studies, being nationwide or local scale, and lack of reporting the age-standardized rate in some studies. Following subgroup analysis, we did not find a significant difference between studies conducted before and after 2006.…”
Section: Discussionmentioning
confidence: 75%